A digital watermarking technique using Discrete Wavelet Transform (DWT) and Singular Value Decomposition (SVD) method with QR Code on Malaysia halal logo / Rosmah Abdul Latif, Suzana Baharudin and Muhammad Anis Abdul Ghani - Abdul Latif, Rosmah; Baharudin, Suzana; Abdul Ghani, Muhammad Anis (Unit Penerbitan UiTM Kelantan, 2019)
Halal is an Arabic word that means allowed or permitted by Islamic laws. Department of Islamic Development Malaysia (JAKIM) is a Malaysian government institution that is responsible to give Halal certification to products which can be consumed by the Muslims. The demand of Halal product in Malaysia is overwhelming, however the procedure to get the Halal certification is not that easy. There are some irresponsible business companies has simply labelled their products with fake version of Halal Logo to deceive Muslim consumers. Therefore, it is crucial to preserve the Halal logo from being manipulated. This paper discusses the use of Watermark technique to enhance the Halal logo characteristic. The digital watermarking method is used in this study. This method is developed by combining the technique of Discrete Wavelet Transform (DWT) and Singular Value Decomposition (SVD). This study has produced a prototype of a Halal logo embedded with a watermark QR code that consists of certification number, expiry date and the company number of a product.The Halal Logo has been tested and, it has shown that the embedded Watermark halal logo has the same appearance with the typical one even though the size of them are different. However, the watermarked Halal Logo cannotbe simply copied as it has a special characteristic. Therefore, it can be concluded that the Watermark method with SVD and DWT techniques could be utilized to increase the imperceptibility and the robustness of an image such as the Malaysia Halal logo